Pengaruh Latihan Kelentukan Punggung Terhadap Kemampuan Service Atas Pada Permainan Sepak Takraw Mahasiswa Pendidikan Jasmani Kesehatan Dan Rekreasi Tahun Akademik 2018 - Salamun, Muhim Hayat; Hasbullah, Bahmid; Latar, Idris Moh (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
This study aims to determine the relationship between waist flexibility and upper serve ability in the game of sepak takraw. The research method used is an experimental method with a form of correlational research. The population of the study was 26 students of Physical and Health Education in the academic year. Data collection in this study used measurement techniques using skills tests. The results showed that the top service ability of the Physical Education students with 16 categories was very good. The ability of waist flexibility has an average result of 8 with good category. Thus, there is a positive effect between waist flexibility and upper serve ability in the game of sepak takraw on the students of Physical and Health Education.